2015
DOI: 10.1038/aps.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Brain protection against ischemic stroke using choline as a new molecular bypass treatment

Abstract: Aim: To determine whether administration of choline could attenuate brain injury in a rat model of ischemic stroke and the underlying mechanisms.Methods: A rat model of ischemic stroke was established through permanent middle cerebral artery occlusion (pMCAO). After the surgery, the rats were treated with choline or choline plus the specific α7 nAChR antagonist methyllycaconitine (MLA), or with the control drug nimodipine for 10 days. The neurological deficits, brain-infarct volume, pial vessel density and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…CDP‐Cho has been shown to reduce oxidative stress by increasing phosphatidylcholine levels through attenuation of phospholipase C activity . In another study, Cho angiogenic property was evidenced by promoting collateral circulation via upregulation of α7 nicotinic acetylcholine receptor, hypoxia‐inducible factor‐1α and vascular endothelial growth factor in permanent MCAo model . In the present study, the CDP‐Cho levels were decreased in MCAo control rats which were found to be elevated in lercanidipine‐treated rats.…”
Section: Discussionsupporting
confidence: 92%
“…CDP‐Cho has been shown to reduce oxidative stress by increasing phosphatidylcholine levels through attenuation of phospholipase C activity . In another study, Cho angiogenic property was evidenced by promoting collateral circulation via upregulation of α7 nicotinic acetylcholine receptor, hypoxia‐inducible factor‐1α and vascular endothelial growth factor in permanent MCAo model . In the present study, the CDP‐Cho levels were decreased in MCAo control rats which were found to be elevated in lercanidipine‐treated rats.…”
Section: Discussionsupporting
confidence: 92%
“…In the brain, α7nAChRs are found in both neurons [ 27 ] and non-neuronal cells such as microglia [ 28 ], astrocytes [ 29 ], and endothelial cells [ 30 ]. When α7nAChRs are stimulated by their agonist choline in a rat stroke model of permanent middle cerebral artery occlusion (MCAO), an elevated amount of α7nAChRs was recognized as well as a reduction of infarct volume and neurological deficits [ 31 ]. In the present study, the number of α7nAChR-expressing cells in the perilesional area did not differ significantly between stimulated and unstimulated animals, indicating that MLR-HFS does not regulate the expression of α7nAChR.…”
Section: Discussionmentioning
confidence: 99%
“…In folate-deficient individuals, more methyl groups are used from choline in methylation of homocysteine (Niculescu and Zeisel, 2002). Choline might also provide protection after ischemic stroke by facilitating angiogenesis (Jin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%